“Marriage is Scary” on TikTok: Maqāṣid al-Sharī'ah's Analysis of the Fear of Marriage in the Digital Era - Sari, Delia Atika; Musyafaah, Nur Lailatul (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
Nowadays, there is a lot of discussion on social media about how